2020
DOI: 10.3390/ma13245648
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Fibrous-Ferrocement Panel Subjected to Flexural and Impact Loads

Abstract: Ferrocement panels, while offering various benefits, do not cover instances of low and moderated velocity impact. To address this problem and to enhance the impact strength against low-velocity impact, a fibrous ferrocement panel is proposed and investigated. This study aims to assess the flexural and low-velocity impact response of simply supported ferrocement panels reinforced with expanded wire mesh (EWM) and steel fibers. The experimental program covered 12 different ferrocement panel prototypes and was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Using a similar approach, the introduced mixes' resistance to repeated impacts following surface cracking was also evaluated in this paper. IDI was defined in earlier research [47,62,63] as the ratio of the failure impact number to the cracking impact number, and this definition was also utilized in the current study, where IDI equals the ratio of A2 to A1 for each combination. Figure 11 depicts the IDI values of four series specimens.…”
Section: Impact Ductility Indexmentioning
confidence: 99%
“…Using a similar approach, the introduced mixes' resistance to repeated impacts following surface cracking was also evaluated in this paper. IDI was defined in earlier research [47,62,63] as the ratio of the failure impact number to the cracking impact number, and this definition was also utilized in the current study, where IDI equals the ratio of A2 to A1 for each combination. Figure 11 depicts the IDI values of four series specimens.…”
Section: Impact Ductility Indexmentioning
confidence: 99%
“…Haist and Ferrara investigated the rheological properties of high-performance FRC during the mixing process and studied the influence of steel fibers on the rheological properties and concluded that thixotropic behaviors increase with the addition of steel fibers [47]. The distribution and orientation of the steel fibers also have an impact on the rheological behavior [25,[48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fiber increased the impact energy absorption and delayed the crack initiation [46]. The steel fibers significantly contributed to arresting crack propagation in the meantime, transmitting the energy effectively [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Fully fibered concrete HPB-2 and HPB-4 were 2318.4 J and 2725.1 J, respectively, had impact energy at the initial crack while compared with the Tension zone fibered concrete HPB-2-T and HPB-4-T were 325.4 J and 488.1 J, respectively.…”
Section: Impact Test Resultsmentioning
confidence: 99%